Perspectives on a way forward for ocean renewable energy in Australia. (November 2018) - Hemer, Mark A.; Manasseh, Richard; McInnes, Kathleen L.; Penesis, Irene; Pitman, Tracey
Abstract: Australia has considerable wave and tidal ocean energy resources. Development of the emerging ocean renewable energy (ORE) industry in Australia offers opportunities to build Australia's blue economy, while actively contributing to committed carbon mitigation measures. Many interdisciplinary challenges are currently hampering development of the industry in Australia, and globally, including technology, cost reduction, policy and regulations, potential for environmental effects, awareness and investment, amongst others. In October 2016, ORE technology and project developers, researchers, academics, policy makers and other stakeholders in Australia's emerging ORE industry came together to identify these challenges and develop possible pathways to grow ocean energy in Australia. Four themes were identified: Technology Development; Education and Awareness; Policy and Regulation; and Finance and Investment. This paper documents the outcomes of the meeting identifying challenges and a way forward against each theme. A key element identified across all themes was the need for stronger coordination across the sector, and the need for a representing body to lead necessary initiatives to support growth and management of the ORE industry in Australia, as one element of a burgeoning blue economy. Highlights: Australia should be an attractive prospect for development of ocean renewables. Challenges and pathways to grow ocean energy in Australia are identified. Four priority themes are Technology; Education; Policy; Investment. Strong coordination across the Australian sector is required to motivate growth.